2010
DOI: 10.1111/j.1365-2516.2009.02129.x
|View full text |Cite
|
Sign up to set email alerts
|

VERITAS‐Pro: a new measure of adherence to prophylactic regimens in haemophilia

Abstract: Prophylactic treatment is recommended for severe haemophilia. Non-adherence to a prophylactic regimen can limit treatment effectiveness and compromise outcomes. The aim of this study is to validate a new prophylactic treatment adherence scale entitled Validated Hemophilia Regimen Treatment Adherence Scale--Prophylaxis (VERITAS-Pro), a self-/parent-report questionnaire consisting of 24 questions on six (four-item) subscales (Time, Dose, Plan, Remember, Skip, Communicate) that takes approximately 10 min to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
184
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(204 citation statements)
references
References 21 publications
14
184
3
3
Order By: Relevance
“…The Validated Hemophilia Regimen Treatment Adherence Scale-Prophylaxis (VERITAS-Pro) [25] is a 24-item measure of self-reported adherence to prophylaxis among people with haemophilia. The scale consists of six sub-scales which examine the extent to which participants take their injections at the recommended time ( Timing ), use the recommended dose ( Dosing ), plan ahead to ensure they have enough supplies ( Planning ), remember to take their injections ( Remembering ), skip injections ( Skipping ) and communicate with the haemophilia centre appropriately ( Communicating ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Validated Hemophilia Regimen Treatment Adherence Scale-Prophylaxis (VERITAS-Pro) [25] is a 24-item measure of self-reported adherence to prophylaxis among people with haemophilia. The scale consists of six sub-scales which examine the extent to which participants take their injections at the recommended time ( Timing ), use the recommended dose ( Dosing ), plan ahead to ensure they have enough supplies ( Planning ), remember to take their injections ( Remembering ), skip injections ( Skipping ) and communicate with the haemophilia centre appropriately ( Communicating ).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that there are different causes of these different types of adherence, but they have not been reliably separated in the literature on adherence to prophylaxis. Therefore, this study aimed to assess adherence reported by YPH themselves, using the VERITAS-Pro (Validated Hemophilia Regimen Treatment Adherence Scale—Prophylaxis [12]) that assesses different dimensions of adherence separately.…”
Section: Introductionmentioning
confidence: 99%
“…The adherence scale study led by Natalie Duncan and Amy Shapiro, both from Indiana Hemophilia and Thrombosis Center, Indianapolis, IN, USA has successfully moved forward with two published articles on the hemophilia regimen adherence scales VERITAS-PRN and VERITAS-PRO [1,2]. There are now new translations of the adherence scales completed in Spanish and Swedish as well as associated studies underway.…”
Section: Update On Inph Project Initiativesmentioning
confidence: 93%
“…I do speak to patients on that level. I hope they did not think I was angry at them when they experienced adherence issues, but I certainly did speak to them about their obstacles, and tried to help them understand that it was not really in their best interest or good for them to miss prophylactic infusions [56,57]. Most children rebel against their parents and their authority; oftentimes, it is easier for someone outside the family unit to say, "This is not what you should fight over-choose something else.…”
Section: Amy Shapiro MDmentioning
confidence: 99%